The Role of Digital Technologies In Shaping Sustainable and Smarter Cities - Berawi, Mohammed Ali; Miraj, Perdana; Sari, Mustika (Universitas Indonesia, 2020)
Digitalization has proven to be important in shaping cities towards more effective and efficient in terms of planning, management, and development. Digitalization that is taking place extensively right now has revolutionized the business ecosystem and changed the value chain process in many industries. It offers various enthralling opportunities yielded by the applications of technologies and intelligent systems to provide smart solutions to urban challenges. The effect of digitalization encouraged innovation by taking into account a physical-digital collaboration among related parties within the urban context and beyond. In a broader context, digital technologies have also played a significant role in accelerating access to more data and knowledge. It further fosters the accountability of institutions, stimulates the efficiency of science, and promotes more innovation opportunities in many sectors. Digital technologies supported by data are used in the development of smart cities to solve problems and make better decisions to achieve a higher urban quality of life. A smart city is an integrated system of six components, which consist of smart people, smart living, smart mobility, smart environment, smart economy, and smart governance; the smartness of which can be enhanced by the utilization of several crucial technologies including information and communication technology (ICT), Internet of Things (IoT), sensor technology, geospatial technology, Artificial Intelligence (AI), and Blockchain.